2012
DOI: 10.1038/onc.2012.336
|View full text |Cite
|
Sign up to set email alerts
|

Bach1 is critical for the transformation of mouse embryonic fibroblasts by RasV12 and maintains ERK signaling

Abstract: Reactive oxygen species (ROS), by-products of aerobic respiration, promote genetic instability and contribute to the malignant transformation of cells. Among the genes related to ROS metabolism, Bach1 is a repressor of the oxidative stress response, and a negative regulator of ROS-induced cellular senescence directed by p53 in higher eukaryotes. While ROS are intimately involved in carcinogenesis, it is not clear whether Bach1 is involved in this process. We found that senescent Bach1-deficient mouse embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…Interestingly, the genes expression signature of the Bach1 -deficient livers disappeared when examined at 100 weeks of age (Figure 3(a)). The 530 gene sets showed overlap with previously published Bach1 knockout signature in MEFs (25 gene entities, Figure 3(b)) [39]. To our surprise, hierarchical clustering of the 25 entities common for both signatures demonstrated that all genes except for Hmox1 returned to the normal levels similar to those in wild-type livers (Figure 3(c)).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, the genes expression signature of the Bach1 -deficient livers disappeared when examined at 100 weeks of age (Figure 3(a)). The 530 gene sets showed overlap with previously published Bach1 knockout signature in MEFs (25 gene entities, Figure 3(b)) [39]. To our surprise, hierarchical clustering of the 25 entities common for both signatures demonstrated that all genes except for Hmox1 returned to the normal levels similar to those in wild-type livers (Figure 3(c)).…”
Section: Resultssupporting
confidence: 54%
“…Also Bach1 -deficient mice are less susceptible to 4-nitroquinoline-1-oxide- (4-NQO-) induced tongue carcinoma than wild-type mice [39]. These observations suggest that higher HO-1 levels may be causal for the tumor-suppressive phenotype of Bach1 deficiency in this experimental model.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with this idea, Bach1-deficient MEFs are resistant to transformation by the H-Ras V12 oncogene and less susceptible to 4-nitroquinoline-1-oxidide (4-NQO)-induced tongue carcinoma than wild-type mice (Nakanome et al 2013). These results suggest that the development of some cancers depends on Bach1 to modulate the gene expression pattern in a favorable way for transformation.…”
Section: Senescence and The Senescence-associated Secretory Phenotypesupporting
confidence: 57%
“…47 One widely accepted hypothesis proposes that the accumulation of oxidative damage arising from endogenously produced ROS leads to cellular senescence, tissue degeneration and age-related disorders. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] In contrast, ΔNp63 has a crucial role in maintaining the proliferative potential of epithelial cells and counteracting cellular senescence and organismal ageing. 40,[63][64][65] Therefore, the molecular mechanism through which ΔNp63 exerts its antisenescence/antiageing functions may be mediated, at least in part, by the activation of antioxidant genes, including CYGB.…”
Section: Discussionmentioning
confidence: 88%